A randomized trial comparing conventional cytology to liquid‐based cytology and computer assistance12. Issue 12 (14th December 2012) - Klug, Stefanie J.; Neis, Klaus J.; Harlfinger, Werner; Malter, Armin; König, Jochem; Spieth, Sibylle; Brinkmann‐Smetanay, Friederike; Kommoss, Friedrich; Weyer, Veronika; Ikenberg, Hans
Abstract Liquid‐based cytology (LBC) has replaced conventional cytology (CC) for cervical cancer screening in some countries. However, it remains unclear whether LBC is superior to CC. A randomized controlled trial was conducted between August 2007 and March 2009 in Germany to compare LBC, alone and in combination with computer‐assisted imaging technology (CAS), to CC in the detection of histologically confirmed cervical intraepithelial neoplasia (CIN). The main outcome measures were detection rates, relative sensitivities, positive predictive values (PPVs) and relative PPVs comparing LBC without and with CAS to CC. Primary histological outcome was CIN2 or higher. Included were 20, 627 women participating in opportunistic cervical cancer screening at 20 gynecologic practices. The practices were randomized weekly to use LBC (n = 11, 331) or CC (n = 9, 296). Patients with positive findings were invited to expert colposcopy. The relative sensitivity of LBC versus CC using the CIN2+ cut‐off was 2.74 (95% confidence interval [CI] 1.66–4.53). The relative sensitivity of LBC/CAS versus CC for CIN2+ was 3.17 (95% CI 1.94–5.19). The PPV of LBC and CC for CIN2+ was 48% and 38%, respectively. The PPV ratio did not differ significantly from unity. Differences between LBC and CC were smaller in some sensitivity and subgroup analyses; however, relative sensitivity of LBC remained increased. LBC without and with CAS compared with CC under the field conditions of an opportunistic screening system had a significantly higher sensitivity for the detection of CIN without deterioration of PPVs. Additional use of CAS did not further improve sensitivity of LBC. © 2012 Wiley Periodicals, Inc.